News agencies as content providers and purveyors of news: A mediahistoriographical study on the development and diversity of wire services - Kenny, Peter (Stellenbosch : University of Stellenbosch, 2009)
Thesis (MPhil (Journalism))--University of Stellenbosch, 2009.